EDUKASI ASI EKSKLUSIF DENGAN MEDIA AUDIOVISUAL PADA IBU DI DESA WEDOROANOM KECAMATAN DRIYOREJO GRESIK - LILIS FATMAWATI; Nurul Fahmi Rizka Laily; Sukma Sofiyan Melati (Akademi Kebidanan Harapan Bunda Bima, 2026)
The low level of breastfeeding promotion means that mothers do not receive complete information about the importance of exclusive breastfeeding. Programs to increase breastfeeding, especially exclusive breastfeeding, have a broad impact on the nutritional status of infants in Indonesia, referring to the breastfeeding program target of 80%. The problem is that mothers are not aware that exclusive breastfeeding alone meets the needs of infants from 0-6 months, and mothers still lack knowledge about the importance of exclusive breastfeeding for infants. For exclusive breastfeeding to be successful, mothers need to have good knowledge and attitudes about exclusive breastfeeding. Therefore, the goal of community service is to provide mothers with knowledge and attitudes about exclusive breastfeeding. This community service activity was carried out by providing education to mothers who have children aged 0-6 months through lectures using audiovisual media. The educational material was presented in the form of attractive audiovisual images and sounds with a delivery that was easy for mothers to understand. The results of this activity showed an increase in knowledge among all respondents (100%) from the “poor” category to 27 (90%) in the “good” category, and an increase in attitudes from the previous ‘negative’ category of 28 (93.3%) to a “positive” category of 30 (100%) after being educated about exclusive breastfeeding.